Body Size Variation in Italian Lesser Horseshoe Bats Rhinolophus hipposideros over 147 Years: Exploring the Effects of Climate Change, Urbanization and Geography - Valeria B. Salinas-Ramos; Paolo Agnelli; Luciano Bosso; Leonardo Ancillotto; Víctor Sánchez-Cordero; Danilo Russo (Biology, 2020)
Body size in animals commonly shows geographic and temporal variations that may depend upon several environmental drivers, including climatic conditions, productivity, geography and species interactions. The topic of body size trends across time has gained momentum in recent years since this has been proposed as a third universal response to climate change along with changes in distribution and phenology. However, disentangling the genuine effects of climate change from those of other environmental factors is often far from trivial. In this study, we tested a set of hypotheses concerning body size variation across time and space in Italian populations of a rhinolophid bat, the lesser horseshoe bat Rhinolophus hipposideros. We examined forearm length (FAL) and cranial linear traits in a unique historical collection of this species covering years from 1869 to 2016, representing, to the best of our knowledge, the longest time series ever considered in a morphological assessment of a bat species. No temporal changes occurred, rejecting the hypotheses that body size varied in response to climate change or urbanization (light pollution). We found that FAL increased with latitude following a Bergmann’s rule trend, whereas the width of upper incisors, likely a diet-related trait, showed an opposite pattern which awaits explanation. We also confirmed that FAL is sexually dimorphic in this species and ruled out that insularity has any detectable effect on the linear traits we considered. This suggests that positive responses of body size to latitude do not mean per se that concurring temporal responses to climate change are also expected. Further investigations should explore the occurrence of these patterns over larger spatial scales and more species in order to detect the existence of general patterns across time and space.